The relationship of tobacco and alcohol use with ageing self-perceptions in older people in Ireland - Amanda Villiers-Tuthill; Antoinette Copley; Hannah McGee; Karen Morgan (BMC, 2016)
Abstract Background Health behaviour patterns in older groups, including tobacco and alcohol use, are key factors in chronic disease prevention. We explore ageing self-perceptions as motivating factors behind smoking and drinking alcohol in older adults, and the complex reasons why individuals engage harmfully in these behaviours. Methods Cigarette and alcohol use was assessed in a large cross-sectional national sample aged 50 years and above from the Irish Longitudinal Study on Ageing (TILDA) (n = 6,576). The Brief Ageing Perceptions Questionnaire (BAPQ) assessed individual's views of their own ageing across five domains. Study hypothesis that stronger beliefs on each of the BAPQ domains would be related to drinking and smoking was examined using multinomial logit models (MNLM). Regression parameter estimates for all variables were estimated relative risk ratios (RRR). Results More women were non-drinkers (30 % vs. 20 %) and men displayed significantly higher alcohol use patterns. One in five older Irish adults was a current smoker (16.8 % of women, 17 % of men), and smoking and harmful drinking were strongly associated (P < .001). Some domains of ageing perceptions were significantly associated with harmful drinking and smoking. While the risk of being be harmful drinker decreased with stronger beliefs about the positive consequences of ageing (RRR 0.89), it increased with higher scores on both emotional representation and control positive domains. Greater awareness of ageing and stronger emotional reaction to ageing increased likelihood of smoking. A greater sense of control over the outcomes of ageing was associated with increased risk of both harmful drinking (RRR control positive 1.16) and smoking (RRR control and consequences negative 1.25). This suggests optimistic bias in relation to perceived health risk from smoking and harmful drinking as a potential adverse effect of perceptions of control. Risks of concurrent smoking and harmful drinking increased with chronic awareness of ageing (RRR 1.24), and negative emotional responses to it (RRR 1.21), and decreased with stronger perceptions of the positive consequences of ageing (RRR 0.85). Conclusions The relationship between ageing perceptions, smoking and drinking is complex. Altering perceptions of ageing may be a useful intervention target aimed at facilitating engagement in preventative health behaviours in older people.